An Energy-Efficient Multiwire Error Control Scheme for Reliable On-Chip Interconnects Using Hamming Product Codes. (15th December 2008) - Fu, Bo; Ampadu, Paul
Abstract : We propose an energy-efficient error control scheme for on-chip interconnects capable of correcting a combination of multiple random and burst errors. The iterative decoding method, interleaver, using two-dimensional Hamming product codes and a simplified type-II hybrid ARQ, achieves several orders of magnitude improvement in residual flit-error rate for multiwire errors and up to 45% improvement in throughput in high noise environments. For a given system reliability requirement, the proposed error control scheme yields up to 50% energy improvement over other error correction schemes. The low overhead of our approach makes it suitable for implementation in on-chip interconnect switches.